Natural rates of teacher approval and disapproval in grade-7 classrooms - Thomas, John D. (1978)
The natural rates of teacher verbal approval and disapproval in ten grade-seven classrooms were determined and compared with those described by White (1975). Although there were differences in the observation techniques used and the behavioral, cultural, and ethnic groups sampled, the results were similar. The majority of the teachers displayed individual rates of disapproval that were higher than their individual approval rates. The correlations between levels of on-task behavior and approval and disapproval rates were low. The issues raised by these findings are discussed in terms of directions for further research.